Adopting Western Culture or Enhancing Indigenous Culture: Takdir Alisyahbana's Discourse on Indonesian Path toward Progress - Hidayat, Herman (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1997)
It was a historical event on Indonesian history, white held a polemic of culture on June 8-10, 1935 in Solo.